Three essays on private capital mobility and financial flows in Sub-Saharan African Countries - (:unkn) unknown (My University, 2023)
Global economy has been characterized by an increasing liberalization of capital markets in recent decades. This liberalization has led to an increase in international capital movements and international financial transactions. Due to the liberalization of capital movements and the opening up of domestic markets, Sub-Saharan African countries are increasingly experiencing substantial international capital inflows. In the 1980s, capital inflows to Sub-Saharan African countries were mainly composed by official development assistance and bank loans to public sectors. In recent years, the composition of these flows has changed to take the form of foreign direct investment and migrant remittances. In parallel with this increase of capital inflows, Sub-Saharan African countries are experiencing substantial capital flight. This thesis, which takes place in an economic context characterized by substantial growth in private capital flows in Sub-Saharan African countries, is organized into three chapters, aiming respectively to answer the following questions : What dynamic links exist between foreign direct investment inflows and domestic private investment ? To what extent does local financial development contribute to the efficient allocation of migrant remittances via domestic private investment ? How does weak banking and financial regulation influence capital flight ? The results of the first chapter show that foreign direct investment has little effect in the short term, but stimulates private investment in the long term. The results also show that foreign direct investment interacts with domestic public investment to reinforce these positive effects. The results also suggest that the impact of foreign direct investment on domestic private investment is stronger in diversified non-resource exporting countries than in countries mainly exporting natural resources. The results of the second chapter show, firstly, that remittances have a positive impact on pr
Keywords: African Research